Implications of Rasa Siddhānta in Digital Storytelling: An Analysis of Selected Episodes of the Web Series ‘Navarasa’ - Kanchan , Manasvi; Raj , Vishakha (Bodhi: An Interdisciplinary Journal, 2024)
Rasa Siddhānta, rooted in the ancient Sanskrit text Nāṭyaśāstra by Bharata Muni, is a fundamental concept in philosophy, art, and communication, focusing on evoking emotional responses known as Rasas. Originally derived from theatre, an audio-visual form of communication, the principles of the theory have transcended time and technology, now influencing contemporary digital platforms such as television, cinema, and OTT services. This study examines the relevance of Rasa Siddhānta in modern digital storytelling through a framing analysis of Netflix’s Tamil anthology series Navarasa, produced by Mani Ratnam and Jayendra Panchapekesan. The study analyzes selected episodes using a systematic random sampling method. The total number of episodes in the web series is nine, and the episode number 2, 4, 6, and 8 are chosen for the study. The research investigates how technical elements such as lighting, costumes, sets, and camera angles align with Bharata Muni’s theory. In this article, theoretical triangulation has been employed for data analysis, using both Rasa Siddhānta and color theory. The findings suggest an alignment between the use of technical elements in digital storytelling and the principles suggested in Bharata Muni’s Nāṭyaśāstra.